The completed work of Christ in John 17:4: an interpretive key for reading the fourth gospel - Redmond, Eric C. (Pickwick Publications, 2025)
"Scholars have viewed Jesus's statement "I have completed the work you called me to do" as a proleptic reference to his work on the cross--that he speaks of it as fully accomplished, for it has been decreed so. Thus, the completed work looks forward to Jesus's cry of "Tetelestai!" from the cross when the work of redemption is done. But what if this is not the best reading of the completed work and the verbal use in John 17:4? What if reading it correctly will reveal something greater about the work of redemption, the glory of the Father, how to read the Fourth Gospel, and how to understand verbal use in the Greek New Testament?" -- Provided by publisher